On the Paradoxical Structure of the Concept of Style. A Theoretical Framework - Steinbach, Tim-Florian (Simmel Studies)

(untitled) (Edizioni ETS, 2023)
In addition to his famous concept of the style of life or lifestyle, Simmel develops a more general concept of style in his writings on art and aesthetics. He makes clear in this context that the concept of style has a paradoxical structure that mediates between the general and the particular and that it always stands for the general. This concept of style allows Simmel to apply it in different research fields: sociology and social philosophy, ethics, art and aesthetics or intellectual history. In developing a theoretical framework for understanding Simmel’s concept of style, we will need to cross these disciplinary boundaries. We will examine the fields of arts and aesthetics as well as intellectual history so as to illustrate how Simmel applies the concept of style. This will also make the paradoxical structure of this concept clear